Dynamics of the students’ physical fitness while studying at higher educational institutions - Griban, G.; Yahupov, V.; Svystun, V.; Dovgan, N.; Yeromenko, E.; Udych, Z.; Zhuravlov, I.; Kushniriuk, S.; Semeniv, B.; Konovalska, L.; Skoruy, O.; Grokhova, G.; et al. (My University, 2020)
The article presents an analysis of the dynamics of the students’ physical fitness while studying at Ukrainian higher educational institutions. The level of physical fitness was assessed by the results in exercises that characterize the development of basic physical qualities: speed qualities (100 m run), speed and power qualities (long standing jump), power qualities (pull-ups, push-ups, and sit-ups for males; flexed arm hang, push-ups, and sit-ups for females), endurance (3000 m run for males and 2000 m run for females), flexibility (bending forward from a sitting position), agility (4 x 9 m shuttle run). The study was conducted in Polissia National University in 2013-2019. 16 groups of the students from the faculties of economics, agronomy, ecology, technology, agricultural management, and agriculture mechanization took part in the study; in total, the research involved 369 students, including 195 males and 174 females. The research methods included the analysis and generalization of scientific, educational and methodical literature on physical education, the methods of conceptual and comparative, system and structural analysis, pedagogical observation, testing, the methods of statistical data processing. The study found that during the period of study at higher educational institutions, both male and female students had no significant improvement in the results of most tests. Moreover, the students’ results in the endurance, power, and flexibility exercises deteriorated. The analysis of the dynamics of the students’ physical qualities development stated that the physical fitness level of the both male and female students of 1st-4th years was generally unsatisfactory. At the same time, the results of females were significantly lower than that one of male students throughout the whole studying period. This indicates a lack of efficiency of the current system of physical education at higher educational institutions of Ukraine. Among the reasons for the decrease in the physical fitness level of senior students are insufficient health and training orientation of physical education; insufficient material and technical base; low motor activity of students; the lack of students’ interests, motives and needs for physical exercises, a low physical state level of school graduates, etc.
Dynamics of the students’ physical fitness while studying at higher educational institutions / G. Griban, V. Yahupov, V. Svystun, N. Dovgan, E. Yeromenko, Z. Udych, I. Zhuravlov, S. Kushniriuk, B. Semeniv, L. Konovalska, O. Skoruy, G. Grokhova, M. Hres, D. Khrystenko, I. Bloshchynskyi // International Journal of Applied Exercise Physiology
Keywords: фізичне виховання, фізична підготовка, фізичні якості,студенти; physical education, physical fitness, physical qualities, students; физическое воспитание, физическая подготовка, физические качества, студенты